DETERMINANT FACTORS OF EARLY ENTREPRENEURIAL DECISION MAKING WITH ACCOUNTING UNDERSTANDING AND THE USE OF ANDROID-BASED ACCOUNTING INFORMATION SYSTEM AS MODERATORS - Eka Sariningsih; Indah Lia Puspita; Chandra Hakiki (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Entrepreneurship is an innovative and creative solution to overcoming Indonesia's unemployment problem. The purpose of this study is to analyze the effect of self-efficacy, e-commerce, and love of money on entrepreneurial decision-making with accounting understanding and the use of Android-based AIS. This study uses a quantitative approach. Using random sampling, the research sample of this study was active students of the accounting department, Faculty of Economics and Management. Using the Slovin formula, the results of 94 respondents. The data collection technique used a questionnaire. The findings reveal that self-efficacy and e-commerce influence early entrepreneurial decision-making among students. Meanwhile, love of money does not have an effect on early entrepreneurial decision-making. Nonetheless, accounting understanding and the use of Android-based AIS are not proven to moderate the influence of self-efficacy, e-commerce, and love of money on early entrepreneurial decision-making. Its moderating effect is not significant for the psychological factors because these are more intrinsic traits not easily altered by system usage. Thus, accounting understanding and Android-based AIS usage enhance the practical execution of decisions influenced by external factors like e-commerce, but do not significantly alter internal motivational factors' influence on entrepreneurial decision-making. Keywords: Self Efficacy, E-Commerce, Love of Money, Accounting Understanding, Use of Android-Based AIS, Entrepreneurial Decision Making